Post-Treatment Trajectories of Retained Totally Implantable Venous Access Ports After Anticancer Therapy: A Conditional Landmark Cohort Study - Zeyang Fan; Tiantian Li; Kai Yang (Current Oncology, 2026)
Background: Retained totally implantable venous access ports (TIVAPs) pose a clinical management challenge after completion of intravenous anticancer therapy, particularly when future treatment needs remain uncertain. We aimed to characterize longitudinal post-treatment TIVAP trajectories after a day-90 conditional landmark, with elective removal prespecified as the primary first event. Methods: This retrospective cohort study included patients who were alive and event-free, retained the original TIVAP, had no documented TIVAP-related indication requiring removal, and had documented clinical and TIVAP status at day 90. Elective removal was the primary event; TIVAP reactivation, complication-related removal, and network-documented death were competing events. Results: Among 1406 patients, the 12-month cumulative incidence was 34.3% (95% confidence interval [CI], 31.4–37.1) for elective removal, 10.1% (95% CI, 8.2–11.9) for reactivation, 4.1% (95% CI, 3.0–5.3) for complication-related removal, and 1.0% (95% CI, 0.5–1.6) for network-documented death. During 1164.9 patient-years, 9978 maintenance-related patient-date encounters were recorded. In the assessed subcohort (n = 1319), 69.2% of assessments indicated willingness to choose a TIVAP again for similar future treatment, 64.4% indicated willingness to recommend TIVAP use, and 26.0% recorded a preference for earlier removal. Conclusions: Retained TIVAPs followed heterogeneous post-treatment courses, including elective removal, subsequent reuse, and continued retention requiring maintenance. These findings describe observed management patterns; they do not establish the comparative effectiveness of retention versus removal or identify an optimal removal time, and they support a prospective evaluation of structured reassessment pathways.